Tinjauan Hukum Terhadap Wali Fasik Perspektif Madzhab Syafi’i: Studi Kasus Kelurahan Tanjung Mulia - Syawaluddin HSB; Sahmiar Pulungan (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
thought, to become a guardian in a marriage, you are required to fulfill several conditions, one of which is that a guardian must be fair (not wicked). However, what often happens in the people of Medan Deli District, in the process of determining a guardian in a marriage, is that people only look at who is the oldest without considering other aspects. Therefore, the aim of this research is to examine the extent to which the legality of a marriage with a guardian to an impious person according to the Shafi'i school of thought, therefore, this is a very important thing to examine, because it is related to whether the marriage is valid or not. This research was conducted in Tanjung Mulia Village. With the formulation of the problem, how is the category of determining the guardian of a wicked marriage, what is the validity of a marriage whose guardian is a wicked person according to the Shafi'i school of thought. This research uses qualitative research with an empirical juridical / sociological juridical approach where the author focuses on the implementation of Islamic legal rules in society. After careful investigation, it turns out that there are cases where the bride-to-be has more than one male sibling who can be a guardian. The results of research show that the community believes that the oldest person has the right and is worthy to be a guardian. In the Shafi'i school of thought there are fair conditions that must be fulfilled as a guardian. there is no guardianship for the wicked. A marriage that takes place using an evil guardian means the marriage is invalid.